2022
DOI: 10.26434/chemrxiv-2022-kzrzz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chiral and Achiral Pendant-Bound Poly(biphenylylacetylene)s Bearing Amide and/or Carbamate Groups: One-Handed Helix Formations and Chiral Recognition Abilities

Abstract: A series of cis-poly(biphenylylacetylene) (PBPA) derivatives bearing chiral and achiral pendant groups at the 4’-position of the biphenyl units through an amide (–NHCO–) or carbamate (–NHCOO–) linker were synthesized by polymerization of the corresponding biphenylylacetylene (BPA) monomers that can be readily prepared in one step from a novel amino-functionalized BPA. An excess one-handed helix induction in the PBPAs through covalent and noncovalent chiral interactions and their chiral recognition abilities wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Such a solvent-induced CD intensity change was frequently observed in PBPAs depending on the chiral and/or achiral pendant groups of PBPAs introduced at the 2,2′,4′-positions of the biphenyl units. 67 In contrast, the previously reported helicity-memorized homopolymers (hpoly-1b, 28,55 h-poly-1c, 27,29 h-poly-1d, 28 h-poly-1e, 28 and hpoly-2 AO 30 ) prepared by the "noncovalent helicity induction and subsequent static memory of the helicity" approach gradually lost their helical sense preference under the same conditions due to the dynamic nature of the helicity memory (Figures 5g and S29). We noted, however, that the elution order of enantiomers can be switched using the helicitymemorized dynamic helical PBPA-based CSPs, 27,28 so that the helicity-memorized PBPA-based CSPs and the present onehanded helical copolymer-based robust CSPs can be used for different purposes since the elution order cannot be switched on the latter CSPs.…”
Section: Chiroptical Properties Of Chiral/achiral Copolymers (Sergean...mentioning
confidence: 67%
See 1 more Smart Citation
“…Such a solvent-induced CD intensity change was frequently observed in PBPAs depending on the chiral and/or achiral pendant groups of PBPAs introduced at the 2,2′,4′-positions of the biphenyl units. 67 In contrast, the previously reported helicity-memorized homopolymers (hpoly-1b, 28,55 h-poly-1c, 27,29 h-poly-1d, 28 h-poly-1e, 28 and hpoly-2 AO 30 ) prepared by the "noncovalent helicity induction and subsequent static memory of the helicity" approach gradually lost their helical sense preference under the same conditions due to the dynamic nature of the helicity memory (Figures 5g and S29). We noted, however, that the elution order of enantiomers can be switched using the helicitymemorized dynamic helical PBPA-based CSPs, 27,28 so that the helicity-memorized PBPA-based CSPs and the present onehanded helical copolymer-based robust CSPs can be used for different purposes since the elution order cannot be switched on the latter CSPs.…”
Section: Chiroptical Properties Of Chiral/achiral Copolymers (Sergean...mentioning
confidence: 67%
“…35 This result indicated that a one-handed helical conformation was almost completely induced in the poly-(R)-3a backbone through the hierarchical chirality transfer from the point chirality of the 1-EE substituents to the axially chiral biphenyl units and further to the main-chain helicity. 35, 67 The absolute helical senses of the one-handed helical PBPAs prepared in this study were unambiguously determined by high-resolution AFM (see below). As anticipated, poly-(+)-3a-Ph, a homopolymer of an optically pure phenylacetylene bearing the same chiral 1-EE substituent ((+)-3a-Ph), showed a negligibly weak CD in toluene at 25 °C (Figure S14), indicating the primary role of the axially chiral biphenyl units of poly-(R)-3a for a one-handed helix induction.…”
Section: Chiroptical Properties Of Chiral/achiral Copolymers (Sergean...mentioning
confidence: 99%